Soldier boy : the Civil War letters of Charles O. Musser, 29th Iowa - Musser, Charles O. (Charles Oliver), 1842-1938 (University of Iowa Press, 1995)
Blood and anger, bragging and pain, are all part of this young Iowa soldier's vigorous words about war and soldiering. A twenty-year-old farmer from Council Bluffs, Charles O. Musser was one of the 76,000 Iowans who enlisted to wear the blue uniform. He was a prolific writer, penning at least 130 letters home during his term of service with the 29th Iowa Volunteer Infantry. Soldier Boy makes a significant contribution to the literature of the common soldier in the Civil War. Moreover, it takes a rare look at the Trans-Mississippi theater, which has traditionally been undervalued by historians.